Power converter with maximum power point tracking MPPT for small wind-electric pumping systems. (June 2015) - Lara, David; Merino, Gabriel; Salazar, Lautaro
Highlights: We implement a wind electric pumping system of small power. The power converter allowed to change the operating point of the electro pump. Two control techniques were implemented in the power converter. The control V / f variable allowed to increase the power generated by the permanent magnet generator. Abstract: In this work, an AC–DC–AC direct-drive power converter was implemented for a wind electric pumping system consisting of a permanent magnet generator (PMG) of 1.3 kW and a peripheral single phase pump of 0.74 kW. In addition, the inverter linear V / f control scheme and the maximum power point tracking (MPPT) algorithm with variable V / f were developed. MPPT algorithm seeks to extract water in a wide range of power input using the maximum amount of wind power available. Experimental trials at different pump pressures were conducted. With a MPPT tracking system with variable V / f, a power value of 1.3 kW was obtained at a speed of 350 rpm and a maximum operating hydraulic head of 50 m. At lower operating heads pressures (between 10 and 40 m), variable V / f control increases the power generated by the PMG compared to the linear V / f control. This increase ranged between 4% and 23% depending on the operating pressure, with an average of 13%, getting close to the maximum electrical power curve of the PMG. The pump was driven at variable frequency reaching a minimum speed of 0.5 times the rated speed. Efficiency of the power converter ranges between 70% and 95% with a power factor between 0.4 and 0.85, depending on the operating pressure.